Survey on Flight Control Technology for Large-Scale Helicopter - Jinshuo Hu; Hongbin Gu (International Journal of Aerospace Engineering)
A literature review of flight control technology is presented for large-scale helicopter. Challenges of large-scale helicopter flight control system (FCS) design are illustrated. Following this, various flight control methodologies are described with respect to their engineering implementation and theoretical developments, whose advantages and disadvantages are also analyzed. Then, the challenging research issues on flight control technology are identified, and future directions are highlighted.